The Role of Spirituality and Values in Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the millennia-old history of our country directly influenced all aspects of its social development, as well as the spiritual values and mentality of our people. The fact that Eastern civilization was created directly on the basis of spirituality, science, morality and spiritual purity, at the same time, the most important reforms in the development of our country are taking place, rapid reforms are following the path of great goals such as the creation of the third Renaissance, and stop at its importance.